Hck/Fgr Kinase Deficiency Reduces Plaque Growth and Stability by Blunting Monocyte Recruitment and Intraplaque Motility. Issue 6 (11th August 2015) - Medina, Indira; Cougoule, Céline; Drechsler, Maik; Bermudez, Beatriz; Koenen, Rory R.; Sluimer, Judith; Wolfs, Ine; Döring, Yvonne; Herias, Veronica; Gijbels, Marjon; Bot, Ilze; de Jager, Saskia C. A.; et al.
Abstract : Background—: Leukocyte migration is critical for the infiltration of monocytes and accumulation of monocyte-derived macrophages in inflammation. Considering that Hck and Fgr are instrumental in this process, their impact on atherosclerosis and on lesion inflammation and stability was evaluated. Methods and Results—: Hematopoietic Hck/Fgr-deficient, LDLr −/− chimeras, obtained by bone marrow transplantation, had smaller but, paradoxically, less stable lesions with reduced macrophage content, overt cap thinning, and necrotic core expansion as the most prominent features. Despite a Ly6C high -skewed proinflammatory monocyte phenotype, Hck/Fgr deficiency led to disrupted adhesion of myeloid cells to and transmigration across endothelial monolayers in vitro and atherosclerotic plaques in vivo, as assessed by intravital microscopy, flow cytometry, and histological examination of atherosclerotic arteries. Moreover, Hck/Fgr-deficient macrophages showed blunted podosome formation and mesenchymal migration capacity. In consequence, transmigrated double-knockout macrophages were seen to accumulate in the fibrous cap, potentially promoting its focal erosion, as observed for double-knockout chimeras. Conclusions—: The hematopoietic deficiency of Hck and Fgr led to attenuated atherosclerotic plaque formation by abrogating endothelial adhesion and transmigration; paradoxically, it also promoted plaque instability by causing monocyte subset imbalance and subendothelial accumulation, raising a note of caution regarding src kinase–targeted intervention in plaque inflammation. Abstract : Supplemental Digital Content is available in the text.